Determination of Interlayer Stresses for Multilayered Materials by using Biquadratic Basic Functions (Journal of Informatics and Mathematical Sciences, 2018)
In this paper, we deal with the boundary value problem for the Lame system, modeling the contact problem for a multilayered material. We use biquadratic basic functions to obtain the transmission conditions on the boundaries of interlayer by the Finite Element Method. We analyze the interlayer stresses.
Keywords: Finite-element analysis; Multilayered Material; Transmission conditions